Dealing with the Proliferation of Bilateral Trade Agreements: Consolidation, Multilateralization, Harmonization, or Dilution? - Jaytan Menon (Asian Development Bank (ADB), 2008)
Bilateral free trade agreements (BTAs) have been proliferating. The outcome of this proliferation of often overlapping BTAs and plurilateral free trade agreements is described as the spaghetti bowl effect or, in the Asian region, the noodle bowl effect. This is costly and welfare-reducing. How should this situation be remedied? This paper evaluates the various options proposed in dealing with the spaghetti bowl. A general limitation of these proposals is their tendency to group all kinds of BTAs together and treat them as a homogeneous group. Thus, the proposals ignore underlying differences in motivation in the formation of BTAs. To overcome this, the paper develops a taxonomy for classifying BTAs by motivation before considering the effectiveness of the different remedies proposed. Each proposal has its pros and cons, and can cater to different types of BTAs. Thus, a combination of the various proposals may be warranted, even in the event of an expeditious and bona fide conclusion to the Doha Round.
hdl:11540/1778
Keywords: 330; Freihandelszone